2009
DOI: 10.1007/s00330-009-1635-8
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tears: should abduction and external rotation (ABER) positioning be performed before image acquisition? A CT arthrography study

Abstract: ABER positioning before CT is associated with improved delineation of partial tears, a higher number of detected tears and modification of treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Third, because all MDCT arthrography and MR arthrography examinations were analyzed by two radiologists in consensus, we did not assess interobserver variation. Fourth, although the number of patients included in this work was similar or even superior to those in previously published prospective studies, the number of each elemental lesion was too small to allow further statistical analysis [10,13].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, because all MDCT arthrography and MR arthrography examinations were analyzed by two radiologists in consensus, we did not assess interobserver variation. Fourth, although the number of patients included in this work was similar or even superior to those in previously published prospective studies, the number of each elemental lesion was too small to allow further statistical analysis [10,13].…”
Section: Discussionmentioning
confidence: 97%
“…In the same way, MDCT arthrography does not detect bone marrow edema in the setting of an acute dislocation. However, despite these disadvantages, this imaging modality has been suggested as a method of choice and is possibly even more accurate than MR arthrography in the preoperative evaluation of anterior shoulder instability [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The ABER view can improve visualization of the glenoid, labrum, and the articular surface of the supraspinatus tendon. 12 High spatial resolution data sets with isotropic resolution (►Table 1) allow for interactive viewing, volume rendering postprocessing technique, and post hoc reconstruction of traditional thick section axial, coronal, and sagittal images with different kernel and window settings. The three-dimensional volume rendering technique can diminish metal artifact and can aid the interdisciplinary and patientphysician communication of the shoulder abnormality.…”
Section: Techniquementioning
confidence: 99%
“…In addition, the posterior glenohumeral translation that occurs in the throwing shoulder in vivo and posterosuperior labral peel-back (80,118). ABER has also been shown to confer greater sensitivity and specificity for detection of partial-thickness rotator cuff tears (119,120) alternative to CT (125). Researchrelated applications have also been reported, such as shear-wave sonoelastography; Takenaga et al not surprisingly found that the posterior/posteroinferior capsules of throwing shoulders in collegiate baseball players were thicker and stiffer than those of the nonthrowing shoulders and that stiffness was more closely correlated to GIRD than thickness (126).…”
Section: Us and Ctmentioning
confidence: 99%